2008
DOI: 10.1007/s00428-008-0642-5
|View full text |Cite
|
Sign up to set email alerts
|

IL-1B −31T>C promoter polymorphism is associated with gastric stump cancer but not with early onset or conventional gastric cancers

Abstract: It has been reported that interleukin-1beta (IL-1B) genes play a crucial role in the genetic predisposition to gastric cancer although there is no information about their role in different subtypes of gastric cancer. We performed single nucleotide polymorphism analysis of IL-1B in 241 gastric cancers including early onset gastric cancers (EOGC), conventional gastric cancers, and gastric stump cancers (GSCs) as well as 100 control patients, using real-time polymerase chain reaction and sequence analysis. The C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Of the remaining 38 publications, three were eliminated, due to reporting duplicate data 17, 18, 19. Ultimately, 37 studies from 35 publications 6, 10, 14, 15, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50 including 6108 cases and 8980 controls were included in the meta‐analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining 38 publications, three were eliminated, due to reporting duplicate data 17, 18, 19. Ultimately, 37 studies from 35 publications 6, 10, 14, 15, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50 including 6108 cases and 8980 controls were included in the meta‐analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, high-level microsatellite instability was significantly more frequent in RGC after Billroth II anastomosis than after Billroth I anastomosis. Sitarz et al reported that the IL-1B-31T [ C promoter polymorphism is associated with RGC but not with early-onset or primary gastric cancer [48]. A statistically significant difference in the presence of the C allele compared with the control group was found in patients with RGC, with the T allele conferring protection against gastric stump cancer.…”
Section: Molecular Carcinogenesis Of Rgcmentioning
confidence: 99%
“…The genetic polymorphism of interleukin-1 ␤ , a proinflammatory cytokine gene, was studied in GC patients. While some studies demonstrated that the most proinflammatory genotypes of interleukin-1 ␤ are positively associated with GC [21] ; other reports do not support these results, which might be explained by the population-specific cancer risks [22] . A polymorphism of interleukin 1 receptor antagonist (IL1RN), IL10 and TNF genes was also identified to be associated with increased risk for GC, which makes it possible to define a specific genetic profile associated with the highest risk for GC [23] .…”
Section: H Pylori Infectionmentioning
confidence: 41%